A low-cost, highly-conductive polyvinyl alcohol flexible film with Ag-microsheets and AgNWs as fillers. Issue 84 (26th August 2016) - Mao, Yongyun; Guo, Junmei; Hu, Changyi; Yang, Hongwei; Yang, Yuwen; Chen, Song
Abstract : Low-cost, high-conductivity flexible conductive films were fabricated using Ag-microsheets, Ag-nanowires (AgNWs) and polyvinyl alcohol (PVA) as conducting agents. The flexible conductive film shows good conductivity under stretching. Abstract : To fabricate the conductive composites with the low resistivity required for conductive films, a multi-layer network of AgNWs must be produced which may not be cost effective. Recently, we have counteracted the problem by using AgNWs and Ag-microsheets to form novel overlapping-junctions-nanostructures, which can significantly improve the electrical properties of conductive films. Subsequently, low-cost, highly-conductivity flexible conductive films were fabricated using Ag-microsheets, Ag-nanowires (AgNWs) and polyvinyl alcohol (PVA) as conducting agents. Interestingly, the interconnected AgNWs and Ag-microsheets within the reciprocal architecture could effectively accommodate strain and show good conductivity under stretching (stretchability of 35%) before they ruptured into patches; thus having major commercial implications.